Oktanting Massage Training And Assistance For Breastfeeding Mothers In Beringin Village, Barito Kuala Regency: Pelatihan Dan Pendampingan Pijat Oktanting Bagi Ibu Menyusui Di Desa Beringin Kabupaten Barito Kuala - meisya deva nadilla; Millati, Rida'; Wulandari, Ni Putu Cindy; Wardana, Ridho Kurnia; Firmansyah, Ahmad; Mariska, Vina (STIKes Hang Tuah Pekanbaru, 2024)
Based on data from Beringin Village, Barito Kuala Regency, 28 stunted children were still found in 2023. The results showed that 38.27% were affected by stunting. One of the factors that causes the high number of stunting cases was due to the suboptimal provision of exclusive breastfeeding. Data from breastfeeding mothers showed that only 5 people (26%) managed to provide exclusive breast milk for up to 2 years out of 14 people (74%) who gave breast milk. The PKM-PM UM Banjarmasin team took the initiative to carry out OKTANTING training and mentoring (Oxytocin Massage, Oketani, and Baby massage to prevent Stunting) which is expected to help reduce the problem of stunting in the village due to non-exclusive breastfeeding. The target of this training was 10 breastfeeding mothers of 11 babies at Posyandu Mawar, Beringin Village. The mentoring period was 3 months. The training method used was demonstration. This mentoring stage was a series of activities, namely establishing a baseline, determining the problem, determining strategic steps, measuring evaluation. The results of this activity were that the flow of breast milk increased from 50% of breastfeeding mothers at the initial meeting to 100% in the last month and an increase in average body weight of 1.43 kg and an increase in body length of 9.95 cm. Abstrak Berdasarkan data Desa Beringin Kabupaten Barito Kuala masih ditemukan anak stunting tahun 2023 sebanyak 28 orang didapatkan hasil bahwa 38,27% yang terkena stunting. Salah satu faktor yang menyebabkan tingginya kasus stunting di dikarenakan ketidakoptimalan pemberian ASI ekslusif, tampak dari data Ibu menyusui jumlah rincian memberikan ASI 14 Orang 74%, berhasil memberikan ASI Eksklusif hingga 2 tahun hanya 5 orang 26%. Tim PKM-PM UM Banjarmasin berinisatif melakukan pelatihan dan pendampingan OKTANTING (Pijat Oksitosin, Oketani, dan Baby massage cegah Stunting) ini diharapkan dapat membantu mengurangi permasalahan stunting di desa tersebut akibat ASI tidak Ekslusif. Sasaran pelatihan ini ialah sebanyak 10 orang ibu menyusui dari 11 bayi dilakukan di Posyandu Mawar Desa Beringin. Waktu pendampingan selama 3 bulan. Metode pelatihan yang digunakan yakni demonstrasi. Tahapan pendampingan ini merupakan rangkaian kegiatan yakni penetapan baseline-penetapan masalah-menetapkan langkah strategis-pengukuran evaluasi. Hasil kegiatan tersebut ialah kelancaran ASI meningkat dari 50% ibu menyusui pada pertemuan awal menjadi 100% di bulan terakhir dan peningkatan berat badan rata rata 1,43 kg serta peningkatan panjang badan 9,95 cm.